An avian transforming retrovirus isolated from a nephroblastoma that carries the fos gene as the oncogene. - Nishizawa, M (1987)
A new avian transforming retrovirus, NK24, was isolated from a chicken with a nephroblastoma. This transforming virus induced fibrosarcomas with osteogenic cell proliferation and nephroblastomas in vivo and transformed fibroblast cells in vitro. From extracts of NK24-transformed cells, anti-gag serum immunoprecipitated a 100-kilodalton nonglycosylated protein with no detectable protein kinase activity. An NK24 provirus present in infected quail cells was molecularly cloned and subjected to nucleotide sequence analysis. The genome of NK24 was 5.3 kilobases long and had a 1,126-base-pair sequence of cellular origin in place of a viral sequence of avian leukosis virus containing the 3' half of the gag gene and the 5' half of the pol gene. Although the entire env gene was retained, it appeared to be inactive, possibly owing to the loss of function of its splice acceptor site as a result of a second deletion of 1,598 bases in the 3' half of the pol gene that extended to the acceptor site. Nucleotide sequence analysis revealed that the NK24 virus contained the fos gene, previously identified as the oncogene of FBJ and FBR murine osteosarcoma viruses. Unlike the v-fos gene products of FBJ and FBR, which suffer a structural alteration at their carboxyl termini, the NK24 v-fos gene product seemed to have the same carboxyl-terminal structure as the chicken c-fos gene product. A comparison of the structures of the products of the NK24 v-fos and mouse c-fos genes suggested that the fos gene product consists of highly conserved regions and relatively divergent regions.